Dinamicheskoe ravnovesie kak faktor povyshenija effektivnosti dvigatel'nyh dejstvij v sporte (na materiale metanija kop'ja) - Kozlova, E.; Klimashevskii, A. (Science in Olympic Sport, 2017)
The article addresses dynamic equilibrium as a factor of increasing the effectiveness of motor actions in sports. On the material of javelin throwing, the regularities of maintenance of a given stable position of the body during the performance of the competitive exercise are revealed. The opportunities are shown for improving the dynamic balance of athletes along with increasing technical mastery, development of motor qualities, enhancing the efficiency of regulation of the activity of the muscles maintaining stability of the lumbosacral complex, improving the activity of the sensory systems on the basis of the use of a wide range of training exercises including elements of competitive activity that most closely approximate in form and structure a competitive exercise; a methodology for their use is given.